Cultural Isnfluence on the Personality of the Lake Vitoria Region’s Community of Kenya. - Sichari, Manson (Archives of Business Research, 2019)
The conceptualization of culture is by no means a simple matter. One possible way to think about culture is that “culture is to society what memory is to individuals. It includes what has worked in the experience of a society, so that it is worth transmitting to future generations. A useful idea such as how to fish is adopted by more and more people to become a culture. Thre are three distinguished kinds of culture: Metaculture, Evoked culture, and Epidemiology culture. The biology that has been common to all humans as a species distinguishable from other species, results in a “metaculture” that corresponds to panhuman mental contents and organization. Biology in different ecologies results in “evoked culture” such as hot climate leads to light clothing. Which reflects the domain of specific mechanisms that are triggered by local circumstances, and leads to within-group similarities and between-groups differences. This can be described as epidemiological culture. Elements of culture are shared standard operating procedures, unstated assumptions, tools, norms, values, habits about sampling the environment, and the like. Because perception and cognition depend on the information that is sampled from the environment and are fundamental psychological processes. This culturally influenced sampling of information is of particular interest to human beings. Cultures develop conventions for sampling information and determine how much to weigh the sampled elements from the environment. For example, people in hierarchical cultures are more likely to sample clues about hierarchy than clues about aesthetics. People in individualist culture, such those of North and Western Europe and North America, sample with high probability elements of personal self e.g. I am busy, I am kind etc. People from collectivist culture such as those from Asia, Africa, and South America, tend to sample mostly elements of the self e.g. my family thinks I am too busy, my co-workers think I am kind. All these kind of behavior or trends are imposed on people b y culture which then becomes their way of life.